2013
DOI: 10.1007/978-3-642-32723-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Time Efficiency in Aerial Swarm Deployment

Abstract: A major challenge in swarm robotics is efficiently deploying robots into unknown environments, minimising energy and time costs. This is especially important with small aerial robots which have extremely limited flight autonomy. This paper compares three deployment strategies characterised by nominal computation, memory, communication and sensing requirements, and hence are suitable for flying robots. Energy consumption is decreased by reducing unnecessary flight following two premises: 1) exploiting environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Using the ideas presented in [14, 15] and [26, 29, 30] an UAV swarm can establish their own communications network. This network can be used for communicating swarm tasks or even to help other robots or a human team for subsequent work [12, 14, 15, 27, 31, 32].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the ideas presented in [14, 15] and [26, 29, 30] an UAV swarm can establish their own communications network. This network can be used for communicating swarm tasks or even to help other robots or a human team for subsequent work [12, 14, 15, 27, 31, 32].…”
Section: Related Workmentioning
confidence: 99%
“…We want to underline that the probabilistic microscopic model and the stigmergy system that will presented here take into account the inherent uncertainty of the real robotic systems, which do not occur in other approaches that assume ideal worlds such as [26, 29, 30]. …”
Section: Related Workmentioning
confidence: 99%
“…From an energetic point of view, we must take into account the difference between the consumption of a UAV in flight or in the standby state. In order to measure individual swarm energy consumption, an energy model, suitable for flying robots is used from [38]. In this model, the energy consumption was split into two parts: the electrical power e f required for flight and the electrical power required to be stationary (landed) e s .…”
Section: Swarm Mobility Behaviormentioning
confidence: 99%
“…In swarm robotics research field, several works for the covering and track-ing tasks can be found, such as those presented in [6,1,10,21,8,34,35]. However, we have found that many of these works do not take into account the special characteristics of the UAVs and therefore are not energetically applicable [6,10,21,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, we have found that many of these works do not take into account the special characteristics of the UAVs and therefore are not energetically applicable [6,10,21,8]. Others works, although were designed for this type of vehicle, are not applicable to the required localization and tracking tasks and are not adapted to the specific needs of non-structured environments, required in marine exploration and jellyfish blooms detection [34,35]. In this article we will propose a swarm behaviour for UAV, that will be formalized with a microscopic model.…”
Section: Introductionmentioning
confidence: 99%